Perbandingan Lama Perendaman Benih Kangkung (Ipomoea Reptans) 6 Jam Dan 12 Jam Terhadap Kecepatan Tumbuh - Desta Ewini Laoli (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This research aims to examine the effect of seed soaking duration on the growth rate of water spinach (Ipomoea reptans) and to determine the most effective soaking period. The study applied an experimental method with two treatments: P1 (6 hours of soaking) and P2 (12 hours of soaking), each using 15 seeds planted in black soil media within recycled plastic bottles. Observations were made for seven days, focusing on the timing of initial germination, the number of seeds that sprouted each day, and the average plant height. The results showed that seeds soaked for 6 hours (P1) exhibited faster and more uniform germination compared to those soaked for 12 hours (P2). P1 also produced slightly taller plants on average. Therefore, a 6-hour soaking period proved more effective in enhancing the early growth of water spinach seeds in a simple cultivation setting.